Land Use/Land Cover Classification in Uruguay Using Time Series of MODIS Images - Baeza, Santiago; Baldassini, Pablo; Bagnato, Camilo; Pinto, Priscila; Paruelo, José (Agrociencia Uruguay, 2020)
The spatial distribution of land use/land cover is the main control of energy, carbon and water dynamics; is also extremely important in environmental monitoring and decision-making in the agricultural sector. The objective of this work was to develop rapid and low cost land use/land cover classifications in Uruguay. We performed decision tree classifications using phenological information derived of NDVI-MODIS (Normal Difference Vegetation Index) time series (period: May 2011-March 2012), field data, and high spatial resolution images (Landsat) to identify «pure» agricultural lots (belonging to a single land use /land cover class). 1.7x107 hectares were classified, discriminating four major categories: Perennial Forage Resources, Afforestation and Forest, Summer Crops, and Winter-Summer Crops; they occupied respectively 63.6, 13.1, 14.3 and 7.4 % of the mapped area. Overall map accuracy was high (89.6 %) and the less accurate class was summer crops (85.8 %). This classification is one of the first descriptions of land use/land cover for the entire Uruguayan territory with high levels of accuracy. The results show a very significant decrease in forage resources occurred in recent years mainly due to the advance of the agricultural frontier. The method used is a fast, repeatable, measurable and inexpensive alternative to describe land use/land cover over large areas and monitor its change over time.